Developing a Normatively Grounded Research Agenda for Fair Trade: Examining the Case of Canada - Reed, Darryl (Journal of business ethics, 2010)
This paper examines two issues related to research of certified fair trade goods. The first is the question of how agendas for fair trade research should be developed. The second issue is the existence of major gaps in the fair trade literature, including the study of the particular features of fair trade practice in individual northern countries. In taking up the first of these issues, the paper proposes that normative analysis should provide the basis for developing research agendas. Such an approach is important to ensure that the necessary types of questions to make normative judgments and policy decisions are posed and that biases that tend to favor mainstreaming practices in the generation of knowledge are minimized. The paper addresses the second research issue by examining the development of research agendas at the level of individual countries, using Canada as a case.